The role of LTBPs in TGF beta signaling. Issue 1 (25th March 2021) - Rifkin, Daniel; Sachan, Nalani; Singh, Karan; Sauber, Elyse; Tellides, George; Ramirez, Francesco
Abstract: The purpose of this review is to discuss the transforming growth factor beta (TGFB) binding proteins (LTBP) with respect to their participation in the activity of TGFB. We first describe pertinent aspects of the biology and cell function of the LTBPs. We then summarize the physiological consequences of LTBP loss in humans and mice. Finally, we consider a number of outstanding questions relating to LTBP function. Key Findings: LTBPs may mediate latent TGFB activation. LTBPs may yield tissue and temporal specificity to latent TGFB activation. LTBPs may control latent TGFB distribution.